The analysis of continuous admissible currents and active power losses in overhead power lines taking into account climatic factors - E. V. Petrova; S. S. Girshin; V. A. Krivolapov; V. N. Goryunov; V. M. Trotsenko (Омский научный вестник)
Formulas for calculating continuous admissible currents and active power losses for overhead power transmission lines under conditions of natural and forced convection for insulated and non-insulated conductors are presented. The correct determination of maximum current loads plays an important role in the efficient use of the load capacity of power transmission lines, and the refinement of the calculation of active power losses is the basis for increasing the efficiency of energy transmission. The results obtained can be used in the selection of measures aimed at increasing the capacity of overhead lines and reducing energy losses.